2022
DOI: 10.52768/2766-7820/2131
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous tumor of transverse colon presenting with colo-colic intussusception in a 24-year old female: Aggressive tumor with a rare presentation in a young female

Abstract: Background: Intussusception is the most common cause of bowel obstruction in the children. However, it is rare in the adults, accounting for only 5% of all cases of bowel obstruction. In Adult Intussusception (AI), an underlying pathology can be demonstrated in majority of the cases. Malignancy is the most common cause of colonic intussusception. We present a case of colonic intussusception due to an underlying primary malignancy in a young female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[7] [9] [15] [16]. Although it has been reported that in these cases adenocarcinoma tends to be of early stages [8], it is more probable that intussusception is only related to tumor size, since larger tumors and/or with invasion to the mesentery or other organs prevent its development [8], and a tumor of small dimensions can present histological characteristics of high risk and even metastatic lymph node disease as in our patient.…”
Section: Up To 38% Of Intussusceptions Develop In the Colon And The M...mentioning
confidence: 79%
See 4 more Smart Citations
“…[7] [9] [15] [16]. Although it has been reported that in these cases adenocarcinoma tends to be of early stages [8], it is more probable that intussusception is only related to tumor size, since larger tumors and/or with invasion to the mesentery or other organs prevent its development [8], and a tumor of small dimensions can present histological characteristics of high risk and even metastatic lymph node disease as in our patient.…”
Section: Up To 38% Of Intussusceptions Develop In the Colon And The M...mentioning
confidence: 79%
“…Fifty-five percent of intussusceptions occur in the small bowel and when they develop due to a tumor, it is generally benign (submucosal lipoma, polyp, leiomyoma, angiolipoma) [ [20]; it has also been described that they can be caused by intestinal feeding tubes, since these can act as a guide point for their formation [12]. Approximately in 20% of the cases no underlying cause can be identified and it is called idiopathic [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations